BEING PROFILED:COGITAS ERGO SUM - Bayamiloglu, Emre; Baraliuc, Irina; Janssens, Liisa; Hildebrandt, Mireille (Amsterdam University Press, 2018)
Profiling the European citizen: why today's democracy needs to look harder at the negative potential of new technology than at its positive potential.